Highway Project Value of Money Assessment under PPP Mode and Its Application - Xiaowei Hu; Juan Han (Journal of Advanced Transportation)
The application of Public-Private Partnership (PPP) mode in transportation infrastructure construction has achieved more progress worldwide; now this mode has been adopted in highway projects of China from 2015. In the application of PPP mode, there are three main facts in China, which include whether the government is responsible for land acquisition and resettlement (LAR), the discount rate changes, and the replacement of business tax by value-added tax (VAT) in 2016. So this paper discusses Value for Money (VFM) quantitative assessment of highway projects under PPP mode in China, which considers currently three actual issues in China. A case study of Heda freeway in China has shown that (1) the government’s responsibility for LAR compensation may attract social capital investor and reduce the risk of social instability, (2) a reasonable range of a low discount rate can greatly reduce government expenditure, and (3) the replacement of business tax by VAT will increase the highway project company’s burden. The research results will be helpful for value of money assessment of highway projects under PPP mode in China and may offer the reference for other countries’ highway projects under PPP mode.